Tricritical point and suppression of the Shastry-Sutherland phase in Ce2(Pd1−xNix)2Sn - Sereni, J.G. (2012)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina